2006
DOI: 10.1007/s11418-006-0029-3
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Sonneratia caseolaris

Abstract: According to the traditional medicinal usage of Sonneratia caseolaris, we tested the extract of S. caseolaris for antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging effect on thin-layer chromatography. Following activity-oriented separation, two flavonoids, luteolin (1) and luteolin 7-O-β-glucoside (2), were isolated. Both of the compounds were found to possess antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 3 publications
2
42
0
6
Order By: Relevance
“…Also, flavonoid has a positive effect of reducing RBC hemolysis, by protecting biological membranes of RBC from free radical which induces oxidative damage (Kitagawa et al, 1992;Asgary et al, 2005). Also, some investigators reported that the antioxidants present in the plant extract might trigger erythropoiesis and antioxidant activity (Shadu et al, 2006;Vargeshe et al, 2010;Lestari & Susanti, 2015). It seems in agreement with the present study as the TCL has flavonoids that capable as an antioxidant which may maintain the heme iron in its ferrous state and this could enhance erythropoiesis (Akah et al, 2008;Uboh et al., 2010;Shatoor, 2011).…”
Section: Blood Profilementioning
confidence: 99%
“…Also, flavonoid has a positive effect of reducing RBC hemolysis, by protecting biological membranes of RBC from free radical which induces oxidative damage (Kitagawa et al, 1992;Asgary et al, 2005). Also, some investigators reported that the antioxidants present in the plant extract might trigger erythropoiesis and antioxidant activity (Shadu et al, 2006;Vargeshe et al, 2010;Lestari & Susanti, 2015). It seems in agreement with the present study as the TCL has flavonoids that capable as an antioxidant which may maintain the heme iron in its ferrous state and this could enhance erythropoiesis (Akah et al, 2008;Uboh et al., 2010;Shatoor, 2011).…”
Section: Blood Profilementioning
confidence: 99%
“…The IC 50 values of 1-3 and 5 and quercetin (positive control) recorded on a microplate reader with DPPH were 60, 28, 50, 500, and 30 lM, respectively. The IC 50 values of DPPH-radical-scavenging assay for compounds 32-39 and the positive control quercetin were 104, 85, 44, 75, 55, 50, 55, 40, and 30 lM, respectively [9][10][11][12].…”
Section: Antioxidant Activitymentioning
confidence: 95%
“…Based on the traditional usage of this plant, we tested the extract for antioxidant activity using the DPPH-radicalscavenging effect on thin-layer chromatography (TLC). Although fatty acids, hydrocarbons, steroids, pectin, and sugars have been previously isolated from this plant [10], by taking the DPPH-radical-scavenging effect as the isolation guide, we isolated a flavone, luteolin (26), and its 7-O-b-glucoside (cynaroside) (27) (Fig. 5).…”
Section: Sonneratia Caseolarismentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the consumption and use of these herbs and fruits, little scientific data clarifying their physiological activities are available. There is some information available relating to their chemical constituents (Goni, 2003;Sadhu, et al, 2006) and biological properties (Scartezzini et al, 2005;Abdille et al, 2004; Lee et al, 2005). Our laboratory has recently reported the antioxidative, antiamylase, antiglucosidase and antihistamine release activities of some Bangladeshi fruits (Hossain et al, 2008).…”
Section: Introductionmentioning
confidence: 99%